Thiazide diuretic-caused hyponatremia in the elderly hypertensive: will a bottle of Nepro a day keep hyponatremia and the doctor away? Study protocol for a proof-of-concept feasibility trial - Ruzicka, Marcel (Pilot Feasibility Stud, 2018)
BACKGROUND: Hypertension is the most common modifiable risk factor for cardiovascular disease, with an increasing prevalence with age, but with easily available medications to control it. Adverse effects of these medications do limit their use, in particular hyponatremia due to thiazide and thiazide-like diuretics. This is more common in the elderly patients due to a combination of inadequate protein intake and impaired urinary dilution capability, made worse by additional thiazide use. Limiting free water intake and increasing protein intake are often not successful resulting in thiazide avoidance. Daily protein supplement is a potential option in this clinical scenario. We describe the protocol for a feasibility study to explore this option. METHODS: This is a single-arm, prospective, open-label proof-of-concept trial, including elderly patients with thiazide diuretic-induced hyponatremia. Forty patients will be enrolled and receive a bottle of a protein supplement daily, providing 120 mmol of solutes and permitting an extra 163 mL free water loss, for 4 weeks. The main outcome measures will be (1) feasibility for enrollment, (2) safety of the intervention, and (3) potential efficacy of the intervention in improving hyponatremia. Secondary outcome measures will include changes in urine osmolality, body weight, and urea measurements. DISCUSSION: Thiazide diuretic-induced hyponatremia is an important adverse effect, with significant clinical impact, such as delirium and falls, and limits the use of these potent antihypertensive agents. There are little data on the effect or safety of protein supplementation and also on whether a trial of this is feasible. The results of this proof-of-concept feasibility trial will help plan and execute a larger definitive trial to test protein supplementation as an effective strategy in this condition. TRIAL REGISTRATION: The trial is registered with Clinical trials, registration identifier: NCT02614807.